The effectiveness of the Blackboard Elements During Corona Pandemic in Light of the Quality Assurance and Accreditation Standards from the Viewpoint of Faculty Members: A Case Study of the Mathematics Department at Umm Al-Qura University - Dr. Yahya Mizher Al Zahrani (University of Science and Technology, Yemen, 2021)
The study aimed to identify the effectiveness of the Blackboard elements during Coronavirus pandemic in light of the quality assurance and accreditation standards from the viewpoint of faculty members at the Mathematics Department, Umm Al-Qura University. To achieve the objectives of the study, the descriptive analytical method was used. The study sample consisted of (45) members of the teaching staff in the mathematics departments of Umm Al-Qura University, who taught mathematics courses during Coronavirus pandemic.  The questionnaire, which consisted of (33) items, was used to collect relevant data. The results of the study indicated that the effectiveness of the four components of the Blackboard that were studied during the Corona pandemic in light of the standards of quality assurance and accreditation was at a medium degree of (3.32), while the effectiveness component of cloud storage on the Blackboard got the highest score (3.68). The effectiveness component of the digital library on the Blackboard got the lowest score among the four elements (3.11). These results suggested the need to increase attention to the requirements of achieving quality assurance and work to raise them in higher education institutions for interactive mathematics courses, as the lack of interest in them may have affected the results and outcomes of mathematics students. The study concluded with a number of recommendations, including supporting the elements of the Blackboard and using them in the educational process, developing and evaluating them in the light of quality standards; conducting further studies on the use of the Blackboard; providing all facilities for the success of the educational process; and seeking to achieve quality and accreditation requirements whenever possible.